(untitled) (Transport systems and technologies, 2019)
The article discusses the practical use of liquid manometers method for bulk carrier vessels draught control. The scientific novelty is the first time performed generalization of author’s practical experience of liquid manometers method use on bulk carrier ships and its theoretical basis. Control of the ship’s draught, heel, and trim, is a constant duty of the responsible ship’s personnel. Especially this control is important during ship’s operations with bulk cargo at the port, where the draught parameters changes rapidly, due to the high rate of loading and unloading on the modern dry bulk terminals. The vessel is required to be in strict compliance with the restrictions imposed by local conditions of navigation in the ports and approaching roadways, as well as the requirements of the International Convention on Load Lines, to the whole vessel’s voyage. The violation of those restrictions may cause the vessel arrest by port authority. It is important for the vessel to be in upright condition, without excessive trim, for the correct determination of onboard bulk cargo amount. The draught marks reading is the most time-consuming element of the vessel’s draught, heel and trim control. In addition, the draught readings on the "facing to the sea" vessel side are unsafe. Known tragic cases among crew members, occurred when they tried to read the draught marks with traditional rope ladders hanged overboard. The practical value of the liquid manometers method is the possibility to define vessel’s draught with greater precision then other known methods. Also, it gives the opportunity to facilitate and make safe the vessel’s draught, heel and trim managing by ship’s cargo mates and shore surveyors during the operations with bulk cargo.